answersLogoWhite

0

y = 3√x

y = 3x^(1/2)

y' = 3(1/2)x^(1/2 -1)

y'= (3/2)x^(-1/2)

y' = 3/[2x^(1/2)]

y' = 3/(2√x)

User Avatar

Wiki User

16y ago

Still curious? Ask our experts.

Chat with our AI personalities

ProfessorProfessor
I will give you the most educated answer.
Chat with Professor
RossRoss
Every question is just a happy little opportunity.
Chat with Ross
BlakeBlake
As your older brother, I've been where you are—maybe not exactly, but close enough.
Chat with Blake

Add your answer:

Earn +20 pts
Q: Differentiate 3 Sq root x
Write your answer...
Submit
Still have questions?
magnify glass
imp